Exploring the association between muscle mass and thyroid function in Chinese community subjects over 45 years old with normal thyroid function: a cross-sectional analysis - Zhu, Zaisheng; Qian, Yidan; Ding, Pan; Jin, Kejia; Chen, Junpeng; Fu, Jiayue; Zhao, Hongjun; Chen, Chengshui; Chen, Junjie (Frontiers in Endocrinology, 2024)
Currently, nothing is known about the connection between muscle mass and thyroid hormone levels in middle-aged and elderly Chinese with normal thyroid function. The purpose of this study was to determine the potential association between muscle mass and thyroid function status in middle-aged and elderly Chinese subjects with normal thyroid function .A cohort of 1868 participants in China were included in this retrospective study; their mean age was 53.97 years, and their skeletal muscle mass index was 7.44 kg/m 2 . Of them, 60.97% were men. Thyroid hormone concentrations, standard biochemical indices, and the frequency of chronic illnesses were among the many factors that were evaluated. Bioelectrical impedance analysis (BIA) was used to assess the patients' body composition. The skeletal muscle index (SMI) was calculated using the following formula: SMI = ASM (kg)/height 2 (m 2 ), where ASM stands for appendicular skeletal muscle mass. To identify the correlations between the variables, the Spearman correlation coefficient was used. Binary logistic regression analysis was conducted to investigate the potential linkages between thyroid hormone levels and diminished muscle mass.In this investigation, a significant correlation was observed between low muscle mass and FT3/FT4 (OR=0.044, 95% CI: 0.004-0.440, P=0.008), as well as FT3 (OR=0.697, 95% CI: 0.508-0.957, P=0.025). Conversely, no discernible correlation trend was detected with TSH (OR=0.972, 95% CI: 0.814-1.160, P=0.753) and FT4 (OR=1.97, 95% CI=0.983-1.224, P=0.1). Following adjustment for various confounding factors, including age, vitamin D levels, triglycerides, HDL-C, LDL-C, total protein, hypertension, diabetes, hyperuricemia, and overweight/obesity, across the entire study population, a positive correlation between SMI and FT3/FT4 was identified. Subsequent gender, age, and weight-stratified analyses revealed consistent correlation trends between SMI and FT3/FT4, with all interactions yielding P-values > 0.05.Our study has revealed that among middle-aged and elderly Chinese individuals exhibiting normal thyroid function, a reduction in the free T3 to free T4 ratio is associated with a decline in muscle mass.